IMPLEMENTASI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM PENGUATAN BUDAYA MUTU DI SD NEGERI 232 TELLESANG - Besse Herlina; Raoda Usman; Hasni; Devi Lupitasari; Andi Rafiah; H. Arman S; Evi Sarfianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the implementation of transformational leadership by the principal in strengthening a culture of quality at SD Negeri 232 Tellesang. The study uses a qualitative approach with a case study type, with research subjects including the principal, teachers, and educational staff. Data were collected through in-depth interviews, observations, and documentation studies, then analyzed through data reduction, data presentation, and conclusion drawing stages, and tested for validity through source and technique triangulation. The results showed that transformational leadership, principals, quality culture, and elementary schools. The dimensions of inspirational motivation and intellectual stimulation were the most dominant aspects in encouraging learning innovation and increasing teacher participation. The implementation of transformational leadership had a positive impact on strengthening the school's culture of quality, which was demonstrated by increased teacher participation in learning communities, improved teacher performance, and the emergence of innovative literacy and digital-based programs. However, the aspect of individual consideration still needs to be improved through more structured mentoring and professional development programs for teachers. This study confirms that the transformational leadership of school principals has a strategic role in building a collaborative, innovative, and continuous improvement-oriented school quality culture.